Technical skills in complex tennis situations: Dutch talented players U15 compared to players U17 - Kolman, Nikki S.; Huijgen, Barbara C. H.; Visscher, Chris; Elferink-Gemser, Marije T. (Frontiers in Sports and Active Living, 2023)
Introduction Technical skills in complex situations appear crucial for progress towards elite tennis performance. However, it is unknown how these skills develop in different age categories in a group of talented youth players. The aim of this study is to evaluate possible differences in technical skills among Dutch talented youth tennis players U15 compared to U17. Methods A total of 19 players (12 males, 7 females; age 14.6 ± 1.4 years) were tested on ball speed, accuracy, percentage errors and spin rate using the on-court Dutch Technical-Tactical Tennis Test. With a ball machine, four games were simulated which were either fixed (game 1 and game 2) or variable (game 3 and game 4), depending on the complexity of the task. Each game consisted of two offensive, two neutral and two defensive rallies, representing different tactical situations. Results A two-way ANOVA revealed a statistically significant interaction between the effects of age category and sex for ball speed (F(1,15) = 5.472, p = 0.034, η2 = 0.267), indicating that males U17 produced higher ball speed compared to males U15, whereas no differences were found between females U15 and U17. A one-way ANCOVA showed that, regardless of sex, players U17 scored significantly higher on accuracy than players U15 (F(1,16) = 5.021, p = 0.040, η2 = 0.239). No differences were found between players U15 and U17 for spin rate and percentage errors (p > .05), although there was a medium to large effect size for males U17 to produce higher spin rates compared to males U15. A closer examination of accuracy revealed that players U17 scored significantly higher compared to players U15 in game 4 (F(1,17) = 6.358, p = .022, η2 = .272) and in defensive situations (F(1,17) = 9.602, p = .007, η2 = .361). Discussion In conclusion, the results of the current study suggest that technical skills, especially ball speed for males and accuracy in complex situations for both males and females, continue to develop in adolescence in talented tennis players. There is an increased understanding about underlying technical skills that contribute to progress towards elite tennis performance. To effectively develop technical skills, coaches are encouraged to design specific practices where these skills are performed in complex situations under high cognitive and temporal pressure.